The "Sugar Tax" Fight - Ricky Telg (Journal of Applied Communications, 2000)
The purpose of this case study was to examine the impact that environmental activism can have on agriculture by focusing on the Florida sugar industry’s reaction during the 1996 “sugar tax” amendment campaign. During the campaign, proponents and opponents of the three proposed Everglades-related amendments to the Florida Constitution spent more than $40 million to sway the public. As a result of the public relations and political campaigns, communicators from Florida agricultural industries realized that they must increase their efforts to project a positive public image